2023
DOI: 10.1186/s12967-023-03945-7
|View full text |Cite
|
Sign up to set email alerts
|

ApoE4 associated with severe COVID-19 outcomes via downregulation of ACE2 and imbalanced RAS pathway

Abstract: Background Recent numerous epidemiology and clinical association studies reported that ApoE polymorphism might be associated with the risk and severity of coronavirus disease 2019 (COVID-19), and yielded inconsistent results. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection relies on its spike protein binding to angiotensin-converting enzyme 2 (ACE2) receptor expressed on host cell membranes. Methods A meta-analysis was conduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 61 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…For example, M1M3M4* haplotype containing risk factor apoE-ε4 and M1M3M6 haplotype containing risk factor apoE-ε3 were found to be associated with risk for AD in small human population (210 AD cases and 159 non-demented elderly controls) using our sister haplotypes and RD test. ApoE-ε3 ( Huang et al, 1995 ; DeMattos et al, 2001 ; Hopkins et al, 2002 ; Sen et al, 2012 ; Pedachenko et al, 2015 ; Mahan et al, 2022 ; Sepulveda-Falla et al, 2022 ; Mulgrave et al, 2023 ) and apoE-ε4 ( Ayyubova, 2023 ; Chen et al, 2023 ; Hamza et al, 2023 ; Koutsodendris et al, 2023 ; Pires and Rego, 2023 ; Sun and Xie, 2023 ; Zhou et al, 2023 ) have been verified to be risk factors for AD. Fallin et al (2001) however found that 3 haplotypes in configure 2 flanking M3 and M4 were significantly associated with risk for AD by using individual-others pairs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, M1M3M4* haplotype containing risk factor apoE-ε4 and M1M3M6 haplotype containing risk factor apoE-ε3 were found to be associated with risk for AD in small human population (210 AD cases and 159 non-demented elderly controls) using our sister haplotypes and RD test. ApoE-ε3 ( Huang et al, 1995 ; DeMattos et al, 2001 ; Hopkins et al, 2002 ; Sen et al, 2012 ; Pedachenko et al, 2015 ; Mahan et al, 2022 ; Sepulveda-Falla et al, 2022 ; Mulgrave et al, 2023 ) and apoE-ε4 ( Ayyubova, 2023 ; Chen et al, 2023 ; Hamza et al, 2023 ; Koutsodendris et al, 2023 ; Pires and Rego, 2023 ; Sun and Xie, 2023 ; Zhou et al, 2023 ) have been verified to be risk factors for AD. Fallin et al (2001) however found that 3 haplotypes in configure 2 flanking M3 and M4 were significantly associated with risk for AD by using individual-others pairs.…”
Section: Discussionmentioning
confidence: 99%
“…RAS operates via the classic ACE/Angiotensin (Ang) II/Ang II type 1(AT1) receptor axis and the non-classical ACE2/Ang 1–7/Mas receptor (MasR) axis. The classical pathway is associated with the impairment of respiratory conditions, while non-classical plays a protective role in COVID-19 complications as ARDS [ 20 , 29 ]. ACE2 as a carboxypeptidase converts the decapeptide angiotensin I (AngI) to Ang (1–9) and the octapeptide Ang II to Ang (1–7) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, using a biolayer interferometry binding assay, a recent study found that ApoE interacts with the RBD of the spike protein in an isoform-independent manner. 56 However, whether the interactions could affect the affinity between ACE2 and the spike protein and subsequently SARS-CoV-2 infection is unknown. In contrast, an in vitro study reported an inhibiting effect of ApoE on SARS-CoV-2 infection.…”
Section: Apoe4 Is a Major Genetic Risk Factor For Sars-cov-2...mentioning
confidence: 99%
“…ApoE4 has been reported to be associated with significant inhibition of ACE2 expression, 67 which may also be one of the reasons for the severity of COVID-19 caused by ApoE4. 56 The increased risk of COVID-19 infection with ApoE4 may partly explain why Black Africans suffer a higher possibility of COVID-19 severity and mortality; the prevalence of the ε4 / ε4 allele is more common in black African individuals (population frequency, 30%–40%) than in Caucasian and Asian individuals (population frequency, 7%–20% and 5%–15%, respectively). 68 , 69 …”
Section: Apoe4 Is a Major Genetic Risk Factor For Sars-cov-2...mentioning
confidence: 99%